2023
DOI: 10.1055/s-0043-1766098
|View full text |Cite
|
Sign up to set email alerts
|

Bone Stress Injuries at the Ankle and Foot

Abstract: Bone stress injuries (BSIs) are a frequent finding in athletes, particularly of the foot and ankle. A BSI is caused by recurring microtrauma to the cortical or trabecular bone exceeding the repair capacity of normal bone. The most frequent fractures at the ankle are low risk, characterized by a low risk for nonunion. These include the posteromedial tibia, the calcaneus, and the metatarsal diaphysis. High-risk stress fractures have a higher risk for nonunion and need more aggressive treatment. Examples are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…The study reported that the functional therapy resulted in excellent clinical outcomes after an average follow-up of 22 months, with no significant differences based on the type of fracture. 38 This approach aligns with the findings of, 39 who suggested that athletes with fifth metatarsal fractures may benefit from surgical screw fixation, leading to optimal healing within approximately 7 to 12 weeks after surgery. However, Baumbach et al demonstrated that functional treatment without stabilization also yielded positive outcomes, emphasizing early return to activities and sports.…”
Section: Discussionsupporting
confidence: 71%
“…The study reported that the functional therapy resulted in excellent clinical outcomes after an average follow-up of 22 months, with no significant differences based on the type of fracture. 38 This approach aligns with the findings of, 39 who suggested that athletes with fifth metatarsal fractures may benefit from surgical screw fixation, leading to optimal healing within approximately 7 to 12 weeks after surgery. However, Baumbach et al demonstrated that functional treatment without stabilization also yielded positive outcomes, emphasizing early return to activities and sports.…”
Section: Discussionsupporting
confidence: 71%
“…Insufficiency stress fractures are more common in women and older patients, even with normal loads on demineralized bone [27]. Metatarsal shafts are the most common site for stress fractures, especially of the second or third rays [43]. Initial radiographs can be negative for up to 2 to 3 weeks.…”
Section: Stress Fracturesmentioning
confidence: 99%
“…Cortical fracture lines and callus formation are better evaluated by radiographs [27]. MRI is the modality of choice, demonstrating periosteal thickening and bone marrow and surrounding reactive soft tissue edema [43]. MRI findings include jagged and irregular, incomplete or complete low signal fracture line through bone, characterized by a band of low signal intensity contiguous with the cortex on both T1 and T2-weighted images.…”
Section: Stress Fracturesmentioning
confidence: 99%